Fiscal Adjustments in OECD Countries : Composition and Macroeconomic Effects - Alesina, Alberto (IMF Working Papers; Working Paper, 1996)
This paper studies how the composition of fiscal adjustments influences their likelihood of 'success', defined as a long lasting deficit reduction, and their macroeconomic consequences. We find that fiscal adjustments which rely primarily on spending cuts on transfers and the government wage bill have a better chance of being successful and are expansionary. On the contrary fiscal adjustments which rely primarily on tax increases and cuts in public investment tend not to last and are contractionary. We discuss alterative explanations for these findings by studying both a full sample of OECD countries and by focusing on three case studies: Denmark, Ireland and Italy.